أهمية المتطلبات البيئية لصادرات سورية من الخضار والفواكه إلى الاتحاد الأوروبي (العنونة والسلامة البيئية الغذائية والتعبئة والتغليف) - ديوب معن; محفوض ماجد محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لا تزال سورية تواجه الإجراءات الحدودية الصارمة التي يفرضها الاتحاد الأوربي على وارداته من الخضار والفواكه. ومن المتوقع أن يحقق سيناريو اتفاقية الشراكة الأوربية المتوسطية تطورًا كبيرًا في القدرة على دخول الأسواق مع أن تلك القدرة سوف تبقى معرضة للقيود الكمية والإدارية. ويشكل دخول الأسواق شرطًا ضروريًا لنجاح التصدير ولكنه غير قادر على تحقيق الفهم الكافي للاتجاهات الحالية لنظام التسويق الحديث السائد حاليًا في الاتحاد الأوربي. وهذا ما دفعنا إلى البحث بمعوقات استعمال قوانين الصحة والصحة النباتية وقوانين الحجر الصحي من قبل الدول الأوروبية كحواجز وقيود غير جمركية على الواردات الزراعية حيث تشترط دول الاتحاد الأوروبي ضرورة تطبيق لوائح صحة النبات على المنتجات الطازجة مثل الخضروات والفاكهة ويمكن أن توفر القدرة على دخول أسواق الاتحاد الأوربي الحافز لتشجيع المصدرين والمنتجين السوريين على التكيف مع المواصفات التي يتطلبها نظام التوزيع الحديث في دول الاتحاد الأوربي. Syrian Exports of fruit and vegetables continue to face stringent Customs and Excise procedures imposed by the European Union. Although the Euro-Mediterranean Economic Partnership is expected to achieve major development in the ability to enter European markets, this scenario is still subject to administrative and quantitative restrictions. Although accessing those markets is necessary for export success, it is still not enough to form sufficient understanding of the current marketing methods prevailing in the European Union. Some of the restrictions are linked to the implementation of health, phytosanitary and plant quarantine laws in European countries which form a barrier, and non-customs restrictions on agricultural imports. The European Union requires fresh products like fruit and vegetables that comply with health and phytosanitary regulations. Entering European markets can be an incentive to encourage Syrian producers and exporters to adapt to the specifications required by the modern distribution system followed in the European Union. This study illustrates the challenges and opportunities arising from compliance with these requirements and identifies measures required to reduce possible negative effects of competitiveness related to the criteria of environment, health and safety.